Die Sextussprüche und ihre Verwandten - Eisele, Wilfried (Sapere (Darmstadt, Germany), 2015)
The sayings ascribed to the philosopher Sextus represent a remarkable example of a Christian revised collection of sayings from the imperial era. They have Pythagorean forerunners and continue to work in Christian monasticism through Evagrius Ponticus. The volume traces these lines of development.